2021
DOI: 10.1038/s41598-021-87916-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal pulse number for theta burst induced change in cortical excitability

Abstract: Theta-burst stimulation (TBS) is a form of non-invasive neuromodulation which is delivered in an intermittent (iTBS) or continuous (cTBS) manner. Although 600 pulses is the most common dose, the goal of these experiments was to evaluate the effect of higher per-dose pulse numbers on cortical excitability. Sixty individuals were recruited for 2 experiments. In Experiment 1, participants received 600, 1200, 1800, or sham (600) iTBS (4 visits, counterbalanced, left motor cortex, 80% active threshold). In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…Indeed, a group recently published a study where healthy subjects received various doses of TBS protocols. 25 In this study, the only TBS protocols which caused statistically significant changes in cortical excitability were 1200 pulses of iTBS, which paradoxically had an inhibitory effect, and 3600 pulses of cTBS, which paradoxically had an excitatory effect. These surprising results highlight the need to better understand and predict individual responses to TBS protocols to try and optimize clinical response to therapeutic protocols.…”
Section: Review Of Basic Principlesmentioning
confidence: 66%
“…Indeed, a group recently published a study where healthy subjects received various doses of TBS protocols. 25 In this study, the only TBS protocols which caused statistically significant changes in cortical excitability were 1200 pulses of iTBS, which paradoxically had an inhibitory effect, and 3600 pulses of cTBS, which paradoxically had an excitatory effect. These surprising results highlight the need to better understand and predict individual responses to TBS protocols to try and optimize clinical response to therapeutic protocols.…”
Section: Review Of Basic Principlesmentioning
confidence: 66%
“…To our knowledge, only one recent study has observed a similar rate of facilitatory responses (i.e., 68%; Guerra et al [ 32 ] following standard iTBS. Most studies using the standard 50 Hz iTBS protocol have reported much lower response rates, including McCalley et al [ 33 ], who recently reported only 33% of responders. It may be argued that high inter-individual response variability will persist regardless of the TBS protocol used in terms of bursting frequency and inter-burst intervals.…”
Section: Discussionmentioning
confidence: 99%
“…However, our goal was not to test overall efficacy but rather to investigate the effectiveness of the modified 30 Hz/6 Hz iTBS protocol in inducing lasting MEP facilitation. Nevertheless, adding a sham condition could provide critical information regarding the influence of expectations and anticipation on individual responses to the modified iTBS protocol [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…TBS protocols consist of bursts that comprise three pulses at 50 Hz that are repeated at 5 Hz. The most common TBS protocol delivers 600 pulses in total, although shorter (i.e., 300 pulses) or longer (i.e., 1800 pulses) variants also exist (Gentner et al, 2008;McCalley et al, 2021). Based on the presence or absence of intermittent stimulation-free periods, we further distinguish between continuous TBS (cTBS) and intermittent TBS (iTBS) (Huang et al, 2005).…”
Section: Different Rtms Protocolsmentioning
confidence: 99%